Reproduction of domestic horses (Equus caballus): The effects of inbreeding, social environment and breeding management - Dubcová, Jana (Jihočeská univerzita, 2015)
This thesis is focused on horse social behaviour and reproduction under human management. First part of the thesis covers issues about reproduction influenced by humans, breeding in restricted areas and artificial processes which can interfere or threaten the domestic horse population survival. These issues are described in lifetime order from conception, through lactation and maternal investment up to weaning, and on the background of detailed information about particular individuals. The second part is focused on social interactions and forming dominance hierarchy within the groups of domestic horses.
Reproduction of domestic horses (Equus caballus): The effects of inbreeding, social environment and breeding management
Keywords: domestic horses; dominance rank; individuality; residence; agonistic behaviour; suckling behaviour; social behaviour; weaning distress; growth; relocation; inbreeding; reproduction; individuality; domestic horses; dominance rank; individuality; residence; agonistic behaviour; suckling behaviour; social behaviour; weaning distress; growth; relocation; inbreeding; reproduction; individuality